Growth, water use and yield of indian mustard (Brassica juncea), gram (Cicer arietinum) and lentil (Lens culinaris) grown as sole crops and intercrops with three moisture regimes - Jana, P K; Mandal, B K; Prakash, Om; Chakraborty, D (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during winter season of 1988-89 and 1989-90 on intercropping indian mustard [Brassica juncea (L) Czernj. & Cosson], gram (cicer arietinum L.) and lentil (Lens culnaris Medikus) on a well-drained sandy-loam soil under 3 levels of irrigation. Indian mustard and legume were planted in ratio 2 : 1, keeping monocrops of indian mustard and legume as the controls. Growth and productivity of indian mustard and legumes were higher than of monocultures. Dry-matter accumulation was the highest (1 117 g/m2) in sole indian mustard. Irrigation led to higher amount of dry-matter accumulation than no irrigation. Two irrigations resulted in the highest leaf-area index in all the cropping systems. Indian mustard + gram intercepted higher percentage of light. Consumptive water Use of indian mustard was higher (31.438 cm) than of gram (25.408 cm) and lentil (25.99 cm). Intercropping indian mustard proved advantageous in utilization of soil moisture under irrigated condition. Moisture extraction from 0-15 cm soil layer was maximum (25.80%) in all the systems of cropping and levels of irrigation. Productivity/unit land of indian mustard + gram or lentil was higher than of the respective monocultures. All intercropping treatments of indian mustard + legumes were greater in relative crowding coefficient, land-equivalent ratio, monetary advantage, relative net return, area-time equivalent ratio and relative value total, giving greater productivity/unit land than monocultures.